Case Report: A rare case of giant gallbladder associated with adverse reactions to anlotinib - Cheng, Jihao; Wang, Xin; Liao, Jingyun; Shen, Yuping (Frontiers in Medicine, 2025)
Giant gallbladder (GGB) is a rare condition that is generally associated with biliary obstruction. GGB induced by chemotherapeutic agents have not been previously reported. This article presents a case of GGB potentially related to adverse effects of anlotinib. The patient was a 74-year-old female who had been taking anlotinib regularly for 2 years following the diagnosis of a malignant lung tumor. The patient was admitted because of abdominal pain accompanied by vomiting and discomfort for 11 days. No fever was observed during onset, but inflammatory markers were abnormally elevated, accompanied by impaired liver function. On physical examination, a tender mass was palpable in the right inguinal region. Abdominal computed tomography showed an enlarged gallbladder (18.6 × 7.2 × 5.3 cm). Enhanced magnetic resonance imaging and magnetic resonance cholangiopancreatography ruled out biliary stones or space-occupying lesions, leading to a final diagnosis of acute cholecystitis with GGB. The patient received antibiotic treatment and anlotinib was immediately discontinued. After 1 week of anti-infective therapy, the abdominal pain resolved, vomiting ceased, liver function and inflammatory markers returned to normal ranges, and the gallbladder regressed to a normal size. To our knowledge, this is the first reported case of GGB associated with anlotinib use. Through a literature review, we conducted an in-depth discussion on the pathogenesis of GGB and the pharmacological effects of anlotinib, with the aim of sharing experiences and alerting clinicians to such adverse events.